Self confidence levels and perception of interns regarding endodontic treatment in different dental colleges of Nepal (Nepal Medical College Journal, 2024)
Endodontic treatment could be considered as one of the most difficult dental procedures in the field of dentistry. It is a sensitive and delicate procedure and its success depends upon multiple steps. Interns may face several obstacles while performing endodontic treatment on the patients. After completion of internship the graduates will be handling cases on their own. Hence, this study was done to know the difficulties faced by interns while performing a root canal treatment. This descriptive cross sectional study was carried out on 230 interns. A specifically designed questionnaire was used to collect socio-demographic details, participants self confidence levels to treat various endodontic procedures, different steps of endodontic treatment as well as to treat different types of teeth, perception of endodontics in terms of difficulty, the most common mishaps encountered during their practice. The participants used a five-point Likert scoring system to indicate their level of confidence as follows: 1= not at all confident, 2= not very confident, 3= neutral, 4= confident, 5= very confident. Descriptive statistics was calculated. They were confident in taking history, diagnosis, injecting local anesthesia, endodontic cavity preparation, radiographic working length determination, shaping root canal with hand files and irrigation. They were neutral on performing root canal treatment on maxillary and mandibular molar. They weren’t very confident in treating tooth resorption and immature apices. They would refer cases to specialist in future and would choose to specialize in endodontics in future. The most common mishap was overestimation and underestimation of working length.